Evaluating the efficacy of alfaxalone in corn snakes (Pantherophis guttatus). (May 2021) - Rockwell, Kelly; Boykin, Kimberly; Padlo, Jordan; Ford, Courtney; Aschebrock, Storm; Mitchell, Mark
Abstract: Objective: Alfaxalone is a popular veterinary anesthetic; however, research on this anesthetic in snakes has been limited to ball pythons, garter snakes and several Australian species. The objective was to evaluate the anesthetic effects of alfaxalone in corn snakes ( Pantherophis guttatus ), a popular pet snake. Study design: Prospective, randomized crossover study. Animals: A total of eight corn snakes. Methods: In phase I, snakes were subcutaneously administered three doses of alfaxalone (5, 10 and 15 mg kg –1 ) in the cranial third of the body to determine the most effective dose. In phase II, a dose of 15 mg kg –1 was administered in the cranial and caudal thirds of the snakes to determine if injection site affected anesthesia duration. Heart rate (HR), respiratory rate ( f R ), righting reflex, escape response, tail pinch, needle prick and tongue flick were monitored at baseline and 5 minute intervals until the snakes fully recovered. Results: Duration of anesthesia differed significantly, with higher doses lasting longer than lower doses: 5 mg kg –1 [23.8 ± 4.4 (15–30) minutes]; 10 mg kg –1 [40.6 ± 9.4 (25–55) minutes]; and 15 mg kg –1 [56.9 ± 8.4 (50–70) minutes], mean ± standard deviation (range). The tail pinch reflex was not completely lost in phase 1. There was a significant change in f R over time, but this was not related to dose. HR was not different by time or dose. Duration of anesthesia was not different after administration of alfaxalone (15 mg kg –1 ) in the cranial third versus the caudal third of the body; however, there was a significant decrease in HR and f R at this dose, regardless of injection site. Conclusions and clinical relevance: Based on these results, alfaxalone (15 mg kg –1 ) provides adequate anesthesia for brief procedures or intubation; however, additional analgesia is required for painful procedures.